20-hydroxyecdysone regulates expression of methioninesulfoxide reductases through transcription factor FOXO in the red flour beetle, Tribolium castaneum. (April 2021) - Ji, Caihong; Zhang, Nan; Jiang, Heng; Meng, Xiangkun; Ge, Huichen; Yang, Xuemei; Xu, Xin; Qian, Kun; Park, Yoonseong; Zheng, Yang; Wang, Jianjun
Abstract: The oxidation of methionine (Met) by reactive oxygen species (ROS) causes detrimental effects on the protein functions. Methionine sulfoxide reductase (Msr) is the secondary antioxidant enzyme involved in protein repair, and is divided into two distinct classes, MsrA and MsrB, although the mechanisms underlying the transcriptional regulation of Msrs remain largely unknown. In this study, the full-length cDNAs encoding MsrA and three alternatively spliced isoforms of MsrB were isolated from the red flour beetle, Tribolium castaneum . Exposure of female adults to oxidative, heat and cold stresses induced expressions of both MsrA and MsrB . RNAi-mediated knockdown of MsrA and MsrB resulted in increased sensitivity of T. castaneum to paraquat-induced oxidative stress. Treatment with 20-hydroxyecdysone (20E) increased expression levels of both MsrA and MsrB . Knockdown of transcription factor forkhead box O ( FOXO ) decreased both MsrA and MsrB mRNA levels and abolished the induction of MsrA and MsrB by paraquat. Luciferase reporter assays revealed that FOXO directly activates the promoters of both MsrA and MsrB . Moreover, paraquat treatment induced expression of two ecdysone biosynthesis genes, Shade and Phantom, 20E upregulated exoression of FOXO, promoted FOXO nuclear translocation，and knockdown of FOXO abolished induction of MsrA and MsrB expression by 20E, suggesting that regulation of MsrA and MsrB by 20E was mediated by FOXO . Overall, these results provide important insights into the transcriptional regulation of insect Msrs . Graphical abstract: Image 1 Highlights: Two methionine sulfoxide reductase genes, MsrA and MsrB, were isolated from Tribolium castaneum. MsrA and MsrB function in oxidative stress tolerance. 20-hydroxyecdysone (20E) induces FOXO expression and nuclear translocation. FOXO upregulates the expression of MsrA and MsrB.